2019
DOI: 10.7554/elife.44358
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ipRGC subpopulations mediate light’s acute and circadian effects on body temperature and sleep

Abstract: The light environment greatly impacts human alertness, mood, and cognition by both acute regulation of physiology and indirect alignment of circadian rhythms. These processes require the melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs), but the relevant downstream brain areas involved remain elusive. ipRGCs project widely in the brain, including to the central circadian pacemaker, the suprachiasmatic nucleus (SCN). Here we show that body temperature and sleep responses to acut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 50 publications
2
62
0
2
Order By: Relevance
“…This is in line with data in mice which demonstrated that sustained neuronal activation induced by active exploration in awake animals leads to an increase in SWA during subsequent sleep [29]. [34]. This corroborates how important the role of the daily cycle of light intensity is in shaping temporal sleep-activity patterns independent of circadian photoentrainment but directly via current ecological and physiological settings [35].…”
Section: Resultssupporting
confidence: 88%
“…This is in line with data in mice which demonstrated that sustained neuronal activation induced by active exploration in awake animals leads to an increase in SWA during subsequent sleep [29]. [34]. This corroborates how important the role of the daily cycle of light intensity is in shaping temporal sleep-activity patterns independent of circadian photoentrainment but directly via current ecological and physiological settings [35].…”
Section: Resultssupporting
confidence: 88%
“…However, how different wavelengths of light activate specific pathways for arousal promotion in humans remains elusive. Interestingly, it has been recently discovered that distinct ipRGC subpopulations mediate light's acute effect on sleep through a circuitry distinct from that of circadian photoentrainment [34]. This corroborates how important the role of the daily cycle of light intensity is in shaping temporal sleep-activity patterns independent of circadian photoentrainment but directly via current ecological and physiological settings [35].…”
Section: Figurementioning
confidence: 73%
“…IpRGCs represent a small population of the total cells in the ganglion cell layer. These cells are the primary regulators of non-image forming processes such as light-induced pupil constriction, circadian photoentrainment, and sleep [4,2]. Based on sequence homology, melanopsin is more closely related to visual pigments found in rhabdomeric photoreceptors found in organisms such as Drosophila [5,1].…”
Section: Introductionmentioning
confidence: 99%